The Development of the Global Conversation Club to Enhance Students’ Intercultural Communicative Competence - Theerasak, Waraporn; Yoon, Rebecca (Arts of Management Journal, 2023)
During the COVID-19 pandemic, international travel was strictly restricted, and international activities were impossible to conduct. In education, an exchange program is what the institutions can offer to support students’ international activities and experiences for the development of their intercultural communicative competence, which is considered vital in the world today. With computer and internet technology, those international activities can be made possible via online platforms. In this regard, the Global Conversation Club has been designed and developed as a virtual meeting where students from different cultural backgrounds can share ideas and information regarding cultural differences. Therefore, this research aims to 1) evaluate the effectiveness of a Global Conversation Club and 2) analyze and present the outcomes of the development and implementation of a Global Conversation Club. This research is qualitative, and the focused-group interview is conducted via Zoom platform to acquire data. The population includes all student participants who join the Global Conversation Club. The results show that the student participants had positive experiences and believed that attending the Global Conversation Club helped them achieve their goals. Consequently, it can be interpreted that Global Conversation Club is effective in offering linguistic, cultural, and intercultural communicative experiences and improvement for the student participants. The researchers highly and respectfully recommend higher education institutions and educators consider Global Conversation Club as a tool to improve students’ intercultural communicative competence. However, it should be kept in mind that the Global Conversation Club should be carefully redesigned so it best fits the goals that each institution, educator, and student may share differently.